Inside the risk management function - Antoncic, Madelyn (Henry Stewart Talks, 2016)
In this interview Dr Antoncic, drawing on her extensive experience with banks and other financial institutions, answers a range of questions concerning the risk function – what can go wrong and how to prevent them going wrong. Issues covered include: market risk, structuring the risk function, handling differences of opinion, the role of governance, the importance of the corporate culture, what happened at Lehman Brothers, selecting risk officers, risk appetite, the importance of knowing what’s going on and risk/trader relationships, among many others.